Extended-spectrum β-lactamase-producing Enterobacterales in diverse foodstuffs: a prospective, longitudinal study in the city of Basel, Switzerland - Gómez-Sanz, Elena; Bagutti, Claudia; García-Martín, Ana B.; Roth, Jan A.; Alt Hug, Monica; Maurer Pekerman, Laura; Schindler, Ruth; Furger, Reto; Eichenberger, Lucas; Steffen, Ingrid; Hübner, Philipp; Stadler, Tanja; et al. (Frontiers in Microbiology, 2023)
The involvement of non-human-to-human transmission of extended-spectrum βlactamase-producing Enterobacterales (ESBL-PE) remains elusive. Foodstuffs may serve as reservoirs for ESBL-PE and contribute to their spread.We aimed to systematically investigate the presence of ESBL-PE in diverse unprocessed foodstuffs of different origin purchased in a central European city.Methods: Chicken and green (herbs, salad, sprouts, vegetables) samples were collected monthly for two consecutive years, from 06/2017 to 06/2019, from large supermarket chains and small local food retailers, representing all ten postcode areas of the City of Basel (Switzerland), and the kitchen of the University Hospital Basel (Basel, Switzerland). After enrichment, presumptive ESBL-PE were isolated by selective culture methods. ESBL-production was confirmed by phenotypic testing.Results: Among 947 food samples, 14.8% were positive for ESBL-PE isolate/s belonging to eight different ESBL-PE-producing bacterial species. Escherichia coli and Serratia fonticola were predominant across samples (9% and 2%). Higher ESBL-PE prevalence was observed in chicken (25.9%) than in green (3.8%) samples (p < 0.001). Among greens, ESBL-PE were most frequently isolated from sprouts (15.2%). High ESBL-PE species diversity was observed among chicken samples, with E. coli as predominant (17.6%). ESBL-producing Enterobacter cloacae was detected among different greens. Yet, ESBL-producing Klebsiella pneumoniae was predominant in sprouts (12.1%). In total, 20.5% of samples from organic farming and 14.2% of samples from conventionally raised animals harbored an ESBLproducing isolate. Detection of ESBL-PE across samples differed between organic and non-organic when stratified by food source (p < 0.001), particularly among greens (12.5% organic, 2.4% conventional). High proportion of organic chicken samples was positive for ESBL-E. coli (33.3%), while the detection of several species characterized the conventional chicken samples. No significant differences in ESBL-PE frequences were detected between national (13.4%) and international samples (8.0%) (p = 0.122). Instead, differences were observed between regions of food production and countries (p < 0.001).Our findings indicate moderate dissemination of ESBL-PE in foodstuffs, especially among chicken and sprouts. We disclose the importance of food type, food production system and production origin when assessing the risk of contamination with different ESBL-PE species.